2006
DOI: 10.1007/s11102-006-9149-8
|View full text |Cite
|
Sign up to set email alerts
|

Decreased GH secretion and enhanced ACTH and cortisol release after ghrelin administration in Cushing’s disease: Comparison with GH-releasing peptide-6 (GHRP-6) and GHRH

Abstract: GH responsiveness to GH secretagogues (GHS) is blunted in Cushing's disease (CD), while ACTH/cortisol responses are enhanced, by mechanisms still unclear. Ghrelin, the endogenous ligand for GHS-receptors (GHS-R), increases GH, ACTH, cortisol and glucose levels in humans. This study evaluated the GH, ACTH, cortisol and glucose-releasing effects of ghrelin in CD in comparison with GHRP-6. GHRH-induced GH release was also studied. Ten patients with CD (BMI 26.9+/-1.0 kg/m(2)) and ten controls (BMI 24.4+/-1.1 kg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
19
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 55 publications
6
19
0
1
Order By: Relevance
“…In our patients with CD GH responses to ghrelin, GHRP-6, and GHRH were blunted, confirming earlier reports by us and others (10,14,15). GH responsiveness to ghrelin was higher in CD and also in controls, which is probably due to the greater potency of this peptide compared to GHRP-6 and GHRH.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our patients with CD GH responses to ghrelin, GHRP-6, and GHRH were blunted, confirming earlier reports by us and others (10,14,15). GH responsiveness to ghrelin was higher in CD and also in controls, which is probably due to the greater potency of this peptide compared to GHRP-6 and GHRH.…”
Section: Discussionsupporting
confidence: 91%
“…It is well known that glucocorticoid excess impairs GH secretion (10). It has been previously shown that GH responses to several stimuli, including ghrelin, GHRP-6, and GHRH, are severely blunted in patients with Cushing's disease (CD) (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Series reported to date have shown ACTH and cortisol-positive responses in patients harboring Cushing's disease (CD) (1)(2)(3)(4)(5)(6)(7)(8), and attenuated or negative responses in patients harboring ectopic ACTH syndrome (EAS) and adrenal cortisol-producing adenomas (1). Such responses have been attributed to the expression of the GH-releasing peptide receptor type 1a (GHS-1a) in corticotrophic tumors (9,10), but there is no study correlating the in vivo response to the pattern of receptor expression.…”
Section: Introductionmentioning
confidence: 99%